I am a man - Hurt, Byron; Jones, Andrew P. (Central Islip, NY : God Bless The Child Productions, 1998)
A 60-minute video that documents the thoughts and feelings of African American men and women from more than 15 cities and towns across America.'I Am A Man' links black men from various socio-economic backgrounds with some of black America's most progressive academics, social critics and authors to provide an engaging, candid dialogue on black masculine identity in American culture.
Title from title screen
Original music composed by Michael Gaskin, Andrew P. Jones
Speakers: bell hooks, Michael Eric Dyson, Kevin Powell, John Henrik Clark, Gail Dines, Hammer, Richard Majors, Jackson Katz, Andrew Young, Monifa Akinwole, Alvin Poussaint
Keywords: African American men -- Conduct of life; African Americans -- Social conditions; African Americans -- Race identity